3(0.7z+3.8)=7(1.5z+7.2)

Simple and best practice solution for 3(0.7z+3.8)=7(1.5z+7.2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(0.7z+3.8)=7(1.5z+7.2) equation:



3(0.7z+3.8)=7(1.5z+7.2)
We move all terms to the left:
3(0.7z+3.8)-(7(1.5z+7.2))=0
We multiply parentheses
0z-(7(1.5z+7.2))+11.4=0
We calculate terms in parentheses: -(7(1.5z+7.2)), so:
7(1.5z+7.2)
We multiply parentheses
7z+50.4
Back to the equation:
-(7z+50.4)
We add all the numbers together, and all the variables
z-(7z+50.4)+11.4=0
We get rid of parentheses
z-7z-50.4+11.4=0
We add all the numbers together, and all the variables
-6z-39=0
We move all terms containing z to the left, all other terms to the right
-6z=39
z=39/-6
z=-6+1/2

See similar equations:

| 3y+1=113 | | 4x+6=9+x | | F(4)=3x-3 | | 1/3x+2=3/6x-4 | | 2w+-11=9w+10 | | 3(1+4x)-2x=83 | | 19-y=11 | | -19=-5+2v | | 226-v=294 | | 289=108-v | | 13.5x=89 | | 13.5x=93 | | -3(1-x)=3x-3 | | x×33=6 | | x+50=1.1x | | 3(2a+3)-2a=(5+2a) | | 31=-y/9 | | -4+3x+10=18 | | x–23=45 | | 5(x+1)-(x-2)=9(x+3) | | 4(10-5x)=3(-3x-5) | | 10-5+5x=25 | | 2(h-3)+5h=5(2+h) | | 15x-47=3x=37 | | d–8=17 | | 5x+2=3x4(2x-1) | | (6w-15)+2w=2(3+4w) | | 6n-3=7n+4 | | 9(m-4)+2m=8 | | 5c+2+7c=38 | | 7x.12=37 | | 14-4(2y+5)=-2y+9 |

Equations solver categories